Strategi Guru Dalam Menanamkan Karakter Disiplin Anak Usia 5-6 Tahun Melalui Metode Reward Dan Punishment - Desri Yanti; Ristiyani Ristiyani (Early Stage, 2026)
This study was motivated by the observation that some children aged 5–6 years at PAUD Al-Kautsar, Damping Village, Pamarayan, had not yet demonstrated optimal disciplinary behavior, as reflected in their lack of compliance with classroom rules, limited participation in learning activities, and insufficient responsibility in completing assigned tasks. This study aimed to describe teachers' strategies for fostering discipline character among children aged 5–6 years through the implementation of reward and punishment at PAUD Al-Kautsar, Damping Village, Pamarayan. The study employed a qualitative approach using a descriptive method. The participants consisted of the principal, Group B teachers, and children aged 5–6 years. Data were collected through observations, interviews, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that teachers fostered discipline character through habituation, role modeling, guidance, supervision, and collaboration with parents, supported by the educational implementation of reward and punishment. Rewards were provided in the form of verbal praise, stickers, and simple appreciation, while punishments consisted of verbal warnings, reminders, and temporary restrictions on playtime. These strategies contributed to improving children's compliance with classroom rules, responsibility in completing tasks, and active participation in learning. The findings provide practical guidance for early childhood teachers in implementing educational reward and punishment strategies to strengthen children's discipline character in daily learning activities.